Compact sub-6 GHz 5G-multiple-input-multiple-output antenna system with enhanced isolation - Saurabh, A.K.; Meshram, M.K. (John Wiley and Sons Inc., 2020)
A compact two-element multiple-input-multiple-output (MIMO) antenna system with improved impedance matching and isolation is presented for future sub-6 GHz 5G applications. The two identical tapered microstrip line fed modified rhombus-shaped radiating elements are placed in the same orientation at a compact substrate area of 0.24λ0 × 0.42λ0 (where, λ0 at 3.6 GHz) on a shared rectangular ground. A remodeled T-shaped ground stub is placed between a pair of radiating element to achieve improved impedance bandwidth and isolation. Further, a split U-shaped stub connected to center of each radiating element to achieve the desired resonant frequency of 3.6 GHz. The proposed antenna covers a −10 dB operating band of 3.34 to 3.87 GHz (530 MHz) with more than 20 dB isolation between a pair of elements. MIMO performances are also analyzed and experimentally validated. The measured performances of a prototype are found in good agreement with simulated performances. Further, the simulation study is carried out to see the effect of housing and extended ground plane on two-element MIMO antenna for practical application. An idea of realization of 12-element MIMO is also studied using the proposed two-element MIMO antenna. © 2020 Wiley Periodicals, Inc.
Keywords: correlation; isolation; multiple-input-multiple-output; mutual coupling; stub; 5G communication